Time in Associative Learning: A Review on Temporal Maps - Chandran, Midhula; Thorwart, Anna (Frontiers in Human Neuroscience, 2021)
Ability to recall the timing of events is a crucial aspect of associative learning. Yet, the traditional theories of associative learning overlooked the role of time in learning association and shaping the behavioural outcome. They addressed temporal learning as an independent and parallel process. Temporal Coding Hypothesis is an attempt to bringing together the associative and non-associative aspects of learning. They proposed the concept of temporal maps, a representation that encodes the summation of several aspects of a learned association, but with considerable importance to the temporal aspect. The temporal maps helps an agent to make inferences about missing information by applying an integration mechanism over a common element present in independently acquired temporal maps. We review the empirical evidence demonstrating the construct of temporal maps and discuss the importance of this concept in behavioural interventions.